Prevalences and configurations of mental disorders among institutionalized adolescents. - Anckarsäter H; Nilsson T; Ståhlberg O; Gustafson M; Saury J; Råstam M; Gillberg C (Developmental Neurorehabilitation)
OBJECTIVE: To assess prevalence figures for psychiatric disorders among institutionalized adolescents due to behavioural problems and/or delinquency. METHOD: Participants were recruited from consecutive referrals to/or treated at two Swedish adolescent units, SIS1 (n = 60) and SIS2 (n = 70) with ranging age of 12-20.3 years (mean age = 16.2; SD = 1.8) during 1 year. Clinical and diagnostic information was used to generate DSM-IV diagnoses. RESULTS: One or several neuropsychiatric disorders were diagnosed in 53% of all subjects: 39% met DSM-IV diagnostic criteria for attention deficit/hyperactivity disorder (AD/HD), 15% for a pervasive developmental disorder (referred to as autism spectrum disorders, ASDs) and 8% had a mental retardation (referred to as a learning disability, LD). The collapsed prevalence for psychiatric disorders requiring specialist attention was 66%, counting severe depression and psychotic disorders but not substance use. About one in three of all adolescents in the study were given psychopharmacological treatment. CONCLUSION: Published studies and this clinical survey clearly indicate that systematic studies of mental health needs among institutionalized adolescents are warranted to form the basis of adequate treatment and support measures.